PENGEMBANGAN MODUL PRAKTIKUM KIMIA DASAR BERBASIS GREEN CHEMISTRY UNTUK MAHASISWA CALON GURU IPA - Arini Siti Wahyuningsih; Jamilatur Rohmah (JURNAL PENA SAINS, 2017)
Environmental conditions are increasingly worrying to make all parties, not least educational practitioners, want give to overcome it. One that can be done is by presenting a learning process that is more concerned about the environment. In science education, the Green Chemistry approach integrated into laboratory activities is expected to address these challenges. Therefore, this study aims to develop a practice Module based on Green Chemistry approach that can be used by prospective students of science teachers as guidance to carry out safe and environmentally friendly lab work on Basic Chemistry course. This research method is Research and Development (RD). The aim of this research is the feasibility of the module based on expert assessment (lecturer of Chemistry) and students. The data of the research were analyzed using quantitative descriptive analysis method. Based on the results of data analysis shows that the developed practice Module is very feasible to be implemented in Basic Chemistry learning because it received an assessment with the category of "very good" from the chemistry lecturer on the three aspects of content, instructions and conformity with the principle of Green Chemistry and get a very positive response from Student responses as users of the module.Keywords: Module lab, Chemistry Basic, Approach of Green Chemistry, student of science teacher candidate